2005
DOI: 10.4049/jimmunol.174.6.3789
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-Dependent Suppression of Experimental Allergic Encephalomyelitis by Th2-Differentiated, Anti-TCR Redirected T Lymphocytes

Abstract: We previously showed that transgenically expressed chimeric Ag-MHC-ζ receptors can Ag-specifically redirect T cells against other T cells. When the receptor’s extracellular Ag-MHC domain engages cognate TCR on an Ag-specific T cell, its cytoplasmic ζ-chain stimulates the chimeric receptor-modified T cell (RMTC). This induces effector functions such as cytolysis and cytokine release. RMTC expressing a myelin basic protein (MBP) 89–101-IAs-ζ receptor can be used therapeutically, Ag-specifically treating murine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Indeed, in a study by Kohm et al (11), suppression of EAE by antigen-nonspecific CD4 ϩ CD25 ϩ regulatory T cells was associated with a Th2 shift among autoreactive lymphocytes. However, in analyses similar to those performed here, we have found that Th2-differentiated RMTC can Th2-deviate the response of autoreactive MBP89-101-specific T lymphocytes (27). This deviation results in greater than four to five times the level of IL-4 production and less than one-third the IL-10 production observed with the use of CD4 ϩ CD25 ϩ RMTC, suggesting that the regulatory cells that we observe here are not exclusively Th2.…”
Section: Cd4supporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, in a study by Kohm et al (11), suppression of EAE by antigen-nonspecific CD4 ϩ CD25 ϩ regulatory T cells was associated with a Th2 shift among autoreactive lymphocytes. However, in analyses similar to those performed here, we have found that Th2-differentiated RMTC can Th2-deviate the response of autoreactive MBP89-101-specific T lymphocytes (27). This deviation results in greater than four to five times the level of IL-4 production and less than one-third the IL-10 production observed with the use of CD4 ϩ CD25 ϩ RMTC, suggesting that the regulatory cells that we observe here are not exclusively Th2.…”
Section: Cd4supporting
confidence: 77%
“…The amount of IL-4 produced was low. Indeed, we have also used Th2-differentiated RMTC to similarly target MBP89-101-specific T cells in vivo, and, when this is done, the MBP89-101-induced IL-4 production is Ϸ5-fold higher than after the use of CD4 ϩ CD25 ϩ RMTC here (27). In contrast to the relatively weak IL-4 production, autoantigen-induced IL-10 production was strongly increased, implying a role for this cytokine in the immunotherapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Other works have shown that protective T reg cells preferentially produce IL-10 (23, [47][48][49]. Clearly, this was not the case here, although some IL-10 was produced by CD25 Ϫ CD4 ϩ T cells.…”
Section: Cd25mentioning
confidence: 39%
“…IL-10 transgenic mice are resistant to EAE, whereas IL-10 Ϫ/Ϫ mice show increased disease severity (44). Th2 T cells ameliorate EAE through IL-10 production (45). CNS IL-10 expression correlates with disease resolution (46).…”
Section: Discussionmentioning
confidence: 99%